In vitro antimicrobial activity of different electrochemicallyactivated solutions on enterococcus faecalis - Ayçe Ünverdi̇ Eldeni̇z; Makbule Bilge Akbulut (Istanbul University, 2019)
PurposeThe aim of this in vitro study was to assess and compare the antimicrobial efficacyof different electrochemically-activated solutions (ECA) and contemporaryirrigants, in root canals infected with Enterococcus faecalis, used with or withoutEndoActivator (EA).Materials and methodsA hundred single-rooted human teeth were prepared. Ninety of the rootsegments were infected with E. faecalis for four weeks, and divided into eighttest groups (n = 10) (four with and four without EA sonication) and a positivecontrol (n = 10). The irrigants tested were electrochemically-activated solutionsproduced by the Medilox® (ECA-MX) and Envirolyte® devices (ECA-EN), 2%CHX and 2.5% NaOCl. The root specimens were irrigated with 5 mL of the testsolution, with additional sonic agitation applied to the EA groups. The dentinesamples that were obtained from the walls were cultured, and the antibacterialefficacy was evaluated by counting the colony-forming units.ResultsThe ECA-EN, 2.5% NaOCl and 2% CHX were more effective than the ECA-MX (p <0.05) with the addition of EA sonication, showing no statistical difference in theelimination of E. faecalis.ConclusionThe ECA-EN shows potential as an endodontic irrigant, while EA usage gives nobenefit in reducing bacteria from root canals.